Practice Frameworks in the Correctional Domain: How Values Drive Knowledge Generation and Treatment - Ward, Tony (International journal of offender therapy and comparative criminology, 2022)
Practice frameworks are a unique type of theory that bridge the gap between abstract explanatory theories, knowledge categories, normative assumptions, and treatment theories. The values component of practice frameworks is particularly critical as it frames the problem space (niches) within which practitioners engage in practice tasks, for example, moral repair, risk reduction, or community integration. It also picks out the specific kinds of entities and their relationships that researchers are most interested in. In effect, values and their related principles play a major role in abstractly mapping out domains of practice while the knowledge related assumptions (e.g., core categories and causal powers) flesh out core entities and processes indicated by these values. In this paper we provide an overview of practice frameworks and examine the role of their normative assumptions in mapping out correctional research and practice tasks.